STAREA SISTEMULUI IMUN ÎN SENESCENŢĂ - Dudnic, Eugen; Paladi, Ecaterina; Budeanu, Liuba (CEP USM, 2008)
As the human body enters old age, the ability to fight off infection and other health problems diminishes significantly. The immune system, which is responsible for fighting infection, simply does not function as efficiently in older adults as in younger people.
Keywords: sistemul imun; imunologia senescenţei